Gender Differences and the Effects of Cooperative Learning in College Level Mathematics - Olson, ViAnn Esther (Curtin University, 2002)
The purpose of this study was to evaluate the effectiveness of cooperative learning in a liberal arts mathematics course and to examine any gender-related differences in the effects of cooperative learning in terms of achievement, composition of the cooperative groups, mathematics anxiety, attitudes toward mathematics, attendance, and retention. The quasi-experimental design compared a control section using individualized learning methods with three treatment sections using cooperative learning methods based on the Learning Together model of Johnson and Johnson (1991). The compositions of the three treatment groups varied: heterogeneous ability/heterogeneous gender, heterogeneous ability/homogeneous gender, and self-selected. The Academic Skills Assessment Program (ASAP) was used as a pre-test to show that the groups were equal. The Revised Math Attitude Scale and the Mathematics Anxiety Rating Scale (MARS) were used as pre- and post-tests to measure changes in attitudes and anxiety. Achievement was measured by individual and group course grades. Group grades were determined by taking 67% of a student's individual exam score plus 33% of the group's average on the exam. Cooperative learning and composition of groups had no significant effect on achievement. The differences between individual and group grades were insignificant, and the group grading method benefited the grades of only five students. Attendance had a large effect on achievement, and the ASAP score and the Math Attitude Post-test were significant predictors of achievement.The MARS post-test was negatively correlated with individual course grade. While no significant gender-related differences surfaced, some trends appeared. The ASAP, MARS, and Math Attitude pre-test scores were equal, however, females achieved slightly higher course grades than males. In each of the four research groups the individual course grades were higher for females than for males. Also, females had a larger decrease in mathematics anxiety with a drop of 22 points compared to the males' drop of 10 points. Males and females each improved their attitudes toward mathematics by only one point, however, in three of the four research groups, females had smaller attitude changes than males, and two of the cooperative learning groups had decreases in their attitude scores.